Effect of S-PRG Eluate on Biofilm Formation and Enzyme Activity of Oral Bacteria - Masahiro Yoneda; Nao Suzuki; Yosuke Masuo; Akie Fujimoto; Kosaku Iha; Kazuhiko Yamada; Tomoyuki Iwamoto; Takao Hirofuji (Hindawi Limited, 2012)
Recently, the antibacterial activity of a composite resin containing prereacted glass ionomer (S-PRG) filler was revealed. We examined the effect of an S-PRG eluate on various biologic activities of Streptococcus mutans and Porphyromonas gingivalis. Adherence ability of S. mutans was evaluated by microtiter plate assay; protease and gelatinase activities of P. gingivalis were examined by synthetic substrate hydrolysis and gelatin film spot assay, respectively. Coaggregation of P. gingivalis with Fusobacterium nucleatum was also examined. S-PRG eluate was found to suppress streptococcal adherence. S-PRG eluate inhibited the protease and gelatinase activities of P. gingivalis and the coaggregation between P. gingivalis and F. nucleatum. These results indicate that S-PRG eluate suppresses streptococcal adherence and inhibits the protease and coaggregation activities of P. gingivalis. These findings may prompt research into novel strategies for preventing caries and periodontitis.